Conference Report: “The Image of Russia in the Balkans”, 7–9 November, Warsaw - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2011)
Sprawozdanie z konferencji / Conference Report: Sajkowski Wojciech, Sprawozdanie z konferencji „The Image of Russia in the Balkans", 7–9 listopada 2011, Warszawa.